Programming and Software Synthesis - Bakshi, Amol B; Prasanna, Viktor K (Architecture-Independent Programming for Wireless Sensor Networks, 2007)
This chapter contains sections titled: Terminology Meta‐Modeling for the ATaG Domain The Programming Interface Compliation and Software Synthesis